Beyond knowledge: how metacognitive awareness shapes clinical judgment in final-year medical students - Bukhari, Gul Mehar Javaid; Pienaar, Abel Jacobus; Victor, Gideon; Khan, Sara (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the correlation between metacognition and clinical reasoning among final-year medical students. Method: The cross-sectional, correlational study was conducted from June to August 2022 at two medical colleges (one public and one private) in Islamabad, Pakistan, after approval from the ethics review boards of Shifa Tameer-e-Millat University, Islamabad, and the Federal Medical Teaching Institute, Islamabad. All final-year medical students at the two institutions were included, and data was collected using structured questionnaires based on metacognitive awareness and diagnostic thinking tools. Data was analysed using SPSS 25. Results: Of the 200 students, 110(55%) were females, 90(45%) were males, 85(42.5%) were aged 23 years, 107(53.5%) were day scholars, 93(46.5%) were living in hostels, and 100(50%) belonged to each of the two participating institutions. A positive linear relationship was found between metacognitive awareness and diagnostic thinking (R2=0.07). Moderate correlations were found between declarative (rho=0.197), conditional (rho=0.064) and procedural knowledge (rho=0.177); comprehension monitoring (rho=0.193); debugging strategies (rho=0.209); and evaluation subscale (rho=0.211). The diagnostic thinking score of private medical college was significantly higher than public medical college (p<0.05), while debugging strategies and evaluation score of public medical college were significantly higher than private medical college (p<0.05). Memory structure, declarative knowledge and information of males, while conditional knowledge of female medical students were significantly high (p<0.05). Conclusion: There was a positive linear relationship between metacognitive awareness and diagnostic thinking among medical students. Overcoming learning challenges, mentoring support, student-oriented teaching, and learning and providing effective clinical exposure can improve clinical reasoning. Key Words: Metacognition, Clinical reasoning, Medical student.